2001
DOI: 10.1007/bf03014962
|View full text |Cite
|
Sign up to set email alerts
|

Neostigmine antagonism of rocuronium block during anesthesia with sevoflurance, isoflurane or propofol

Abstract: Purpose: To examine the influence of continuing administration of sevoflurane or isoflurane during reversal of rocuronium induced neuromuscular block with neostigmine.Methods: One hundred and twenty patients, divided into three equal groups, were randomly allocated to maintenance of anesthesia with sevoflurane, isoflurane or propofol. Neuromuscular block was induced with rocuronium and monitored using train-of-four (TOF) stimulation of the ulnar nerve and recording the force of contraction of the adductor poll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…neuromuscular block appears more rapid in TIVA than in general anesthesia with volatile anesthetics [10,11]. Wulf et al reported that interactions of rocuronium and volatile anesthetics resulted in augmentation of the intensity of neuromuscular block but did not result in significant effects on duration of recovery of the block [5].…”
Section: Discussionmentioning
confidence: 98%
“…neuromuscular block appears more rapid in TIVA than in general anesthesia with volatile anesthetics [10,11]. Wulf et al reported that interactions of rocuronium and volatile anesthetics resulted in augmentation of the intensity of neuromuscular block but did not result in significant effects on duration of recovery of the block [5].…”
Section: Discussionmentioning
confidence: 98%
“…Inhalation anesthetics enflurane [ isoflurane [ halothane[ TIVA potentiate the effects of rocuronium. Some studies have reported that the presence of volatile agents prolongs the time to disappearance of neuromuscular blockade provided by rocuronium and that this effect is more significant in case of sevoflurane usage [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…neostigmine) and the cyclodextrine sugammadex are available at present. Although proven to be an effective antagonist, acetylcholinesterase inhibitors failed to reverse neuromuscular blockade in the presence of inhalational anesthetics [64]. If used without monitoring of neuromuscular function, neostigmine was shown to have an opposite effect, leading to impairment in respiratory function and a consecutive increase in the incidence of PPCs [15 & ].…”
Section: Neuromuscular Blockade and Reversalmentioning
confidence: 99%